Readings on the Definition and Arguments towards Atheism among Muslim Theologians and Philosophers - Mohamad Fuad, Mohamad Razif; Hamat, Mohd Fauzi; Che Nordin, Mohd Khairul Naim; Qatawneh, Mohammad Abdelhamid Salem (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This study aims to discuss a preliminary analysis of responses by classical and contemporary Muslim scholars on Atheism and New Atheism and identify the approaches that have been taken by them. It also elucidates on type of arguments used by those scholars. While there are many studies about Atheism, New Atheism, and Islam, few or none of them preliminary analysed the works of classical and contemporary Muslim scholars. Selected books written by classical and contemporary Muslim scholars on Atheism and New Atheism were preliminarily reviewed and examined. This study found that the critiques of classical and contemporary Muslim scholars are constructive, systemic, and systematic in upholding the ʿaqīdah. Five renowned and essential rational arguments that are frequently used by classical and contemporary Muslim scholars are the ontological argument, argument from contingency, kalām cosmological argument, teleological argument, and moral argument. The researcher also believes that these respective arguments must also undergo reform (islāh), renewal (tajdīd), and constant improvement in areas or matters that are subject to change over time (mutaghayyirāt).